SECURITY COOPERATION BETWEEN THE EUROPEAN UNION AND THE REPUBLIC OF TURKIYE - Tučić, Boris; Dragišić, Radmila (Politeia, 2024)
By utilising the theoretical framework of the science of international relations and by relying on selected scientific methods, such as the content analysis, comparative and inductive method, the paper analyses the security cooperation between Turkiye and the European Union.. The analysis comprises two levels: at the first one, the focus is on the position and status of the Republic of Turkiye within relevant EU Common and Security Policy structures, such as PESCO projects, European Defense Agency Programmes, and military missions and operations led by the EU or within the EU – NATO partnership or the EU security and defense industry programmes; at the second one, the subject of the analysis are the positions of Turkiye and the EU regarding the most important issues of contemporary international relations and security, such as the Ukrainian war, the conflict in Gaza and general relations in the Middle East, the  relationship with the Russian Federation, as well as the most important factors determining the positions of the two sides in this context. One of the conclusions of the analysis implies that the great potential for the EU – Turkiye security cooperation has not been efficiently fulfilled because of numerous reasons, such as historically accumulated disagreements between Turkiye, on the one side, and some EU member states, on the other, differences between the two sides in the field of their identities and basic social, cultural and political values, as well as a continuously false EU strategic approach towards Turkiye and its status regarding the EU structures and policies. The EU must recognise Turkiye in its full capacity as a regional power and treat it as an equal, constructive partner. If not, especially taking into account monumental global geopolitical changes, the relations between the two sides might become even more deteriorated, with further negative impacts on their security cooperation.
Keywords: Turkiye; European Union; CFSP; CSDP; Ukranian conflict; war in Gaza strip